Internalisasi Nilai Perdamaian pada Kurikulum Pendidikan Tinggi - Yuliyanto Yuliyanto (Badan Strategi Kebijakan Hukum, 2015)
The rise of cases of violent conflict in the student cause public unrest. To minimize such conflicts need to be instilled in students the values of peace which can be obtained by students through higher education curriculum. In the context of creating it, and then in the education world need to insert three important aspect, namely cognitive, affective and psychomotor. Cognitive aspects relating to wit or intellect; aspect affective related to feelings and emotions; while the psychomotor includes the ability of skill physical in do or finish a job. The purposes of this study are: (1) to determine the formulation of development policy of peace carried out in universities (portrait of three colleges in West Kalimantan); and (2) to determine the strategies and methods that are relevant in the values of peace which have implications for the prevention of violence. This study used qualitative research methods by using in-depth interviews to collect data. The study recommends to the Directorate General of Higher Education to develop a constructive pattern in integrating curriculum in the Universities to internalize the values of Peace.